How do social practices shape policy? Analysing the field of 'migration as adaptation' with Bourdieu's 'Theory of Practice'. Issue 4 (21st August 2017) - Ober, Kayly; Sakdapolrak, Patrick
Abstract : In recent decades, there has been a shift in the climate‐migration discourse: from one preoccupied with 'climate refugees' to one of 'migration as adaptation'. Academics and policy‐makers alike see migration as a way to generate income, diversify livelihoods, and spread risk in the face of climate change. Past literature has found that policy prescriptions at this nexus may play into existing politics and framings, especially in the struggle for funding or in the age of the ever‐present neoliberal agenda. This paper makes the case that perhaps the machinations behind policy recommendations need not appear to be sinister. While higher‐level structural considerations should be taken into account and doubtless undergird the trajectory of policy‐making, organisations often follow existing pathways neither because of empirical evidence nor with malicious intent, but rather because it is part and parcel of existing practices of positioning themselves within the system and playing the rules of the game. In fact, every‐day and seemingly mundane practices can accumulate and 'hang together' to shape and determine policy outcomes. This happens in a variety of ways in the field of 'migration as adaptation', but in its most explicit form can be unveiled in the organisational practices of writing publications and participating in conferences and working groups, for example. By using a practice‐oriented approach, with Bourdieu's 'Theory of Practice' as a guide, this paper provides an understanding of the logic and practices of the migration‐as‐adaptation policy sphere and the limited policy prescriptions related to it as well as suggests sites at which to target interventions for more radical policy imaginings.